Performance deviations and acquisition premiums: The impact of CEO celebrity on managerial risk‐taking - Cho, Sam Y.; Arthurs, Jonathan D.; Townsend, David M.; Miller, Douglas R.; Barden, Jeffrey Q. (Strategic Management Journal, 2016)
Research summary: This article draws on identity control theory and a study of acquisition premiums to explore how CEO celebrity status and financial performance relative to aspirations affect firm risk behavior. The study finds that celebrity CEOs tend to pay smaller premiums for target firms, but these tendencies change when prior firm performance deviates from the industry average returns, thereby leading these CEOs to pay higher premiums. The study also finds that the premiums tend to be even larger when celebrity CEOs have more recently attained celebrity status. Taken together, these findings contribute to identity control theory and CEO celebrity literatures by suggesting that celebrity status is a double‐edged sword and that the internalization of celebrity status by CEOs strongly influences the decision‐making of CEOs . Managerial summary: The purpose of this article is to examine how CEO celebrity status and financial performance relative to aspirations affect the size of acquisition premiums. The study finds that celebrity CEOs tend to pay smaller premiums for target firms. However, when celebrity CEOs ' prior firm performance is either better or worse than the industry average, these CEOs pay higher premiums. This situation is exacerbated when the CEO has only recently been crowned a celebrity. In effect, these CEOs feel great pressure to match the inflated performance expectations that come with celebrity status. These findings suggest that being a celebrity is a double‐edged sword. The implication here is that CEOs who have recently been crowned a celebrity should be aware of these pressures and cope accordingly. Copyright © 2015 John Wiley & Sons, Ltd.